Linearity and stationarity of South Asian real exchange rates - Liew, Venus Khim Sen; Lee, Hock Ann; Lim, Kian Ping; Lee, Huay Huay (2006)
The linearity and stationarity of the real exchange rates of India, Nepal, Pakistan and Sri Lanka are investigated using formal linearity and the recently developed nonlinear stationary test procedures. Results obtained show that these real exchange rates are stationary albeit the presence of nonlinearity.